2014
DOI: 10.1177/147470491401200311
|View full text |Cite
|
Sign up to set email alerts
|

Husband's Esteem Predicts his Mate Retention Tactics

Abstract: delity or prevent their defection from the relationship. These tactics include low-risk acts that render the current relationship more attractive by bestowing benefits on the woman, as well as cost-inflicting acts that render defection from the relationship risky or dangerous for her. Previous research has linked men's mate retention behavior with men's mate value (value as a current or potential partner) using women's reports. The current research addresses limitations of that research using self-reports and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 34 publications
(92 reference statements)
2
15
0
1
Order By: Relevance
“…In addition, contingent self‐esteem often drives self‐esteem level in that successes and failures in the domain of contingency (e.g., relationships) lead to fluctuations in self‐esteem level (Crocker & Wolfe, ). Thus, RCSE may moderate the association between self‐esteem level and mate retention behavior that has been observed in previous work (Holden, Shackelford, et al, ).…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…In addition, contingent self‐esteem often drives self‐esteem level in that successes and failures in the domain of contingency (e.g., relationships) lead to fluctuations in self‐esteem level (Crocker & Wolfe, ). Thus, RCSE may moderate the association between self‐esteem level and mate retention behavior that has been observed in previous work (Holden, Shackelford, et al, ).…”
Section: Introductionsupporting
confidence: 54%
“…The results of Study 1 showed that self‐esteem level was positively associated with benefit‐provisioning behaviors and negatively associated with cost‐inflicting behaviors (see also Holden, Shackelford, et al, ). Consistent with our hypotheses, RCSE was positively associated with both benefit‐provisioning and cost‐inflicting behaviors.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Mate retention behaviours are often performed to reduce the likelihood of partner infidelity and relationship termination (Buss and Shackelford 1997), which can vary between sexes. For example, in research exploring men's use of mate retention behaviour in marriages, it has been found that a husband's self-esteem predicts likelihood of engaging in mate retention tactics (see Holden et al 2014). Furthermore, recent evidence suggests that those who have anxious attachment styles often engage in mate retention behaviours (Barbaro et al in press).…”
Section: Mate Value and Mate Retention Behaviourmentioning
confidence: 99%
“…En el caso de los hombres las categorías iden ficadas sólo en ellos fueron: pasión y porque su pareja le es significa va, mismas que vistas desde la perspec va de las Teorías del Refuerzo, remarcan las atracciones, las recompensas, las sa sfacciones o los refuerzos que ob enen de la relación, es decir aquello percibido como un beneficio y que fomentan la sa sfacción con la relación (Maner, Gailliot, & Miller, 2009), así mismo se ha observado, en estudios anteriores, que para el sexo masculino la sa sfacción con su pareja, el interés y la pasión que despiertan su pareja, son fuertes predictores para la permanencia relacional (Holden et al, 2014). Las mujeres, sin embargo, mencionaron que se debe permanecer para para ser plenas, esta dimensión esta mazada por el ideal cultural de la relación de pareja, en la que la que se considera que cada individuo necesita a "su media naranja" para complementarse y/o realizarse a través del establecimiento de una familia propia, especialmente esta premisa ene un importante peso cultural para las mujeres, en las que el paradigma de la maternidad es visto como el ideal de realización personal (Díaz Guerrero, 2003).…”
Section: Discussionunclassified